2022
DOI: 10.1021/acssuschemeng.2c05627
|View full text |Cite
|
Sign up to set email alerts
|

Direct Synthesis of Ethylene and Hydrogen from CO2 and Ethane over a Bifunctional Structured CaO/Cr2O3-V2O5/ZSM-5 Adsorbent/Catalyst Monolith

Abstract: In this study, we synthesized bifunctional adsorbent/catalyst materials (BFMs) consisting of a CaO adsorbent admixed with Cr2O3-V2O5/ZSM-5 catalysts. The obtained BFMs were further formulated, processed, and shaped through additive manufacturing (3D printing) method. The physical and chemical properties of structured CaO/Cr2O3-V2O5/ZSM-5 adsorbent/catalyst monoliths were thoroughly characterized and evaluated. The effects of operating conditions including reaction temperature, ethane composition, and space ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 67 publications
1
12
0
Order By: Relevance
“…The IPD model fitting was performed by maximizing the R value for each curve, which were in the range of 0.88–0.99%. As evident, for both MOF-74 and UiO-66 samples, the adsorption data were fitted poorly to the single straight line, implying that the intraparticle diffusion was not the rate-limiting step, rather, the intraparticle diffusion model fitting was found to be mostly multilinear, indicating that adsorption kinetics was controlled by multiple processes including (i) external surface adsorption, (ii) intraparticle diffusion, and (iii) final equilibrium steps. The k id estimated from this nonlinear analysis was found to be in the ranges of 0.66–1.90 and 0.34–1.04 mg/g·min 1/2 for MOF-74 and UiO-66, respectively (see Table ).…”
Section: Resultsmentioning
confidence: 96%
“…The IPD model fitting was performed by maximizing the R value for each curve, which were in the range of 0.88–0.99%. As evident, for both MOF-74 and UiO-66 samples, the adsorption data were fitted poorly to the single straight line, implying that the intraparticle diffusion was not the rate-limiting step, rather, the intraparticle diffusion model fitting was found to be mostly multilinear, indicating that adsorption kinetics was controlled by multiple processes including (i) external surface adsorption, (ii) intraparticle diffusion, and (iii) final equilibrium steps. The k id estimated from this nonlinear analysis was found to be in the ranges of 0.66–1.90 and 0.34–1.04 mg/g·min 1/2 for MOF-74 and UiO-66, respectively (see Table ).…”
Section: Resultsmentioning
confidence: 96%
“…Given that the dehydrogenation activity of VO x -based catalysts was found to be intimately related to the reducibility of surface VO x , which increases with a decrease in the VO xsupport interactions, the effects of the support matrix on the molecular structure of VO x have been investigated. 85,[127][128][129][130][131] In the study by Shan, et al, 123 they found that VO x supported on ZrO x possessed the highest CO 2 -OPDH activity and was the easiest to be reduced compared to VO x supported on Al 2 O 3 , MgO and SiO 2 . Similarly, Nakagawa et al 120 loaded 5% V on different supports and performed CO 2 -OPDH at 550 °C, and found that the activity of the catalysts followed the order of VO x supported on diamond oxide > Al 2 O 3 > activated carbon > SiO 2 , which is consistent with their reducibility orders.…”
Section: Supported Vanadium Oxidesmentioning
confidence: 99%
“…The global chemical industry produces over 170 million tons of ethylene (C 2 H 4 ) each year, typically by thermal decomposition or steam reforming of ethane (C 2 H 6 ). To purify the produced C 2 H 4 , downstream cryogenic distillation is required to remove small amounts of co-existing C 2 H 6 . Considering how energy-intensive this separation process is, significant efforts have been made to replace it with non-thermal methods, such as membrane separation or adsorption. In particular, C 2 H 4 /C 2 H 6 separation via adsorption over nanoporous materials has been touted as a promising technology to improve energy efficiency of this process. , However, adsorptive separation of light olefins/paraffins still remains in its infancy despite significant advances that have been made in sorbents design and discovery over the past few decades.…”
Section: Introductionmentioning
confidence: 99%